Using inerter-based control device to mitigate heave and pitch motions of semi-submersible platform in the shallow sea. (15th March 2020) - Ma, Ruisheng; Bi, Kaiming; Hao, Hong
Highlights: Rotational inertia dampers are proposed to control both the heave and pitch motions of SSP. Performances of fixed heave plate (FHP), tuned heave plate (THP) and RID are studied and compared. The RIDs can provide almost the same or even better control performance with a smaller physical mass. Abstract: Semi-submersible platforms (SSPs) are widely applied for energy mining in the ocean. During its service life, SSP may be subjected to excessive heave and pitch motions induced by sea waves, which in turn may result in fatigue problems of structural components or even catastrophic capsizing of the platform. It is therefore important to mitigate the heave and pitch motions of SSP by all means. In the present study, a novel inerter-based control system, rotational inertia damper (RID), is proposed to simultaneously mitigate the heave and pitch motions of SSP in the shallow sea. The responses of SSP equipped with RID systems subjected to six typical wave conditions are calculated in the frequency and time domains respectively based on the developed analytical models and Simulink models. For comparison, the models and responses of SSP without and with traditional control devices, i.e. fixed heave plate (FHP) and tuned heave plate (THP), are also developed and calculated. The results reveal that the RID system can achieve almost the same or even better control effectiveness compared to the conventional systems with a much smaller additional mass to the SSP especially when the SSP is under harsher waves.